Coefficient inequalities of certain class of univalent functions / Bryn Darren Johnny, Muhammad Firdaus Norisham and Muhammad Syafiq Najmie Yusaini - Johnny, Bryn Darren; Norisham, Muhammad Firdaus; Yusaini, Muhammad Syafiq Najmie (2022)
Geometric function theory is a part of complex analysis that aims to study the geometric properties of certain class of univalent functions. It is not easy task to determining geometric properties since it involves many theorems and the definition. Many classes of functions that can be explore on the study of geometric function. This study focused on defining new generalized subclass of analytic univalent function. However, there are only a few methods that can be used to solve this problem. The Herglotz Representative Theorem method is used to determine geometric properties of this function.